HARMONISASI SYARI’AT DAN HAKIKAT DALAM PENERAPAN HUKUM ISLAM DI INDONESIA: KAJIAN FALSAFAH TASYRI - Hisbullah Hisbullah; Hanaping; Misbahuddin; Sabri Samin; Andi Moh. Rezki Darma; Mulham Jaki; Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2022)
Shari'ah and Hakikah are two sciences in Islam that are seen as conflicting sciences. The science of Shari'ah which is oriented to the deeds of human birth and the science of hakikah oriented to the inner deeds of man. Both tend to be viewed differently in their practice. However, if understood and explored, the two sciences have a very close relationship and cannot be separated from practice. Man consisting of both lahiriyah and batiniyah elements desperately need both knowledge to achieve the goal of human creation, namely worship and worship God. The science of Shari'ah as a form of embodiment of human slavery through concrete behavior, while the science of nature as the embodiment of human slavery through abstract and only known emotional and inner activities of the individual who does it. Through the fusion of shari'ah and hakikah, the application of Islamic law can be enforced in a mannered manner with law enforcement through a method of gentle approach or upholding ihsan. The enforcement of Islamic law with ihsan has been enforced since the time of the Prophet Muhammad (peace be upon him), enforcement in a polite manner is expected to uphold the sharia law of Islam to all human beings around the world without any violence and compulsion.